Pregnant women's perceptions of gestational weight gain: A systematic review and meta‐synthesis of qualitative research. Issue 4 (21st November 2016) - Vanstone, Meredith; Kandasamy, Sujane; Giacomini, Mita; DeJean, Deirdre; McDonald, Sarah D.
Abstract: Excess gestational weight gain has numerous negative health outcomes for women and children, including high blood pressure, diabetes, and cesarean section (maternal) and high birth weight, trauma at birth, and asphyxia (infants). Excess weight gain in pregnancy is associated with a higher risk of long‐term obesity in both mothers and children. Despite a concerted public health effort, the proportion of pregnant women gaining weight in excess of national guidelines continues to increase. To understand this phenomenon and offer suggestions for improving interventions, we conducted a systematic review of qualitative research on pregnant women's perceptions and experiences of weight gain in pregnancy. We used the methodology of qualitative meta‐synthesis to analyze 42 empirical qualitative research studies conducted in high‐income countries and published between 2005 and 2015. With this synthesis, we provide an account of the underlying factors and circumstances (barriers, facilitators, and motivators) that pregnant women identify as important for appropriate weight gain. We also offer a description of the strategies identified by pregnant women as acceptable and appropriate ways to promote healthy weight gain. Through our integrative analysis, we identify women's common perception on the struggle to enact health behaviors and physical, social, and environmental factors outside of their control. Effective and sensitive interventions to encourage healthy weight gain in pregnancy must consider the social environment in which decisions about weight take place.